Novel maleic anhydride derivatives: liquid crystalline materials with enhanced mesomorphic and optical characteristics - Ahmed, Hoda A.; Abolibda, Tariq Z.; Ismail, Yasser A. M.; Almohammedi, Abdullah; Aly, K. A.; Ibrahim, Mohamed S.; Gomha, Sobhi M. (Frontiers in Chemistry, 2023)
A new class of liquid crystalline materials, 4-(2,5-dioxo-2,5-dihydro-1H-pyrrol-1-yl)phenyl 4-(alkoxy)benzoates (Mn), derived from maleic anhydride, was synthesized and studied for mesomorphic and optical properties. These materials consist of three derivatives with varying terminal flexible chain lengths (6 to 12 carbons) linked to the phenyl ring near the ester bond. The study employed differential scanning calorimetry (DSC) and polarized optical microscopy (POM) to characterize the mesomorphic properties. Molecular structures were elucidated using elemental analysis, FT-IR, and NMR spectroscopy. The findings reveal that all the synthesized maleic anhydride derivatives exhibit enantiotropic nematic (N) mesophases. The insertion of the heterocyclic maleic anhydride moiety into the molecular structure influences the stability and range of the N phase. Additionally, entropy changes during N-isotropic transitions are of small magnitude and exhibit non-linear trends independent of the terminal alkoxy chain length (n). This suggests that the ester linkage group does not significantly promote molecular biaxiality, and the clearing temperature values are relatively high. By comparing the investigated materials with their furan derivatives found in existing literature, it was established that the substitution examined in this study induces the formation of nematic phases.